(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
The effect of glyphosate-chemical residues on Nicotiana tabacum L. growth and development has been studied via treating the soil, before transplanting tobacco seedlings, using several concentrations (0, 4, 360 g/h) of the herbicide. The 360 g/h treatment conducted to many negatives effects in all the studied growth stages (after 10, 20, 30 and 40 days of transplanting), as indicated by the decrease of leaves water content (%), plant height (cm/plant), leaves number (leaves/plant), leaf area (cm2), plant leaf area (cm2/plant), specific leaf weight (g/cm2), leaf area index, the net photosynthesis (g/m2/day) and the stress tolerance indices (ST) as well as the increase of stress intensity evaluated as (SI= 1-(YS/YC)) compared with 4 g/h and control treatments. In contrast, 4 g/h treatment improved tobacco growth and development, as revealed in all the physiological, morph-physiological and morphological traits that are measured after 10 days of transplanting. These results indicate that glyphosate herbicide has a very negative effect on tobacco plants growth and can lead to increase the absent-plants level when used by high concentrations, while in the low doses; it could stimulate cell division, plant growth and development. تأثير المعاملة بالمبيد العشبي (جليفوسات)على الصفات الفيزيولوجية والمورفيزيولوجية لدى نبات التبغ (Nicotiana tabacum L.) درس العمل الأثر الكيميائي المتبقي لمبيد الأعشاب، جليفوسات، في نمو وتطور نبات التبغ (Nicotiana tabacum L.) صنف البلدي، وذلك بمعاملة التربة قبل أسبوع من تشتيل البادرات بتراكيز مختلفة (0، 4 و360 غ/هكتار) من المبيد العشبي، جليفوسات. أدت المعاملة بالتركيز المرتفع (360 غ/هكتار) لتأثيرات سلبية ذات أثر معنوي في أغلب مراحل نمو وتطور نباتات التبغ (بعد 10، 20، 30 و40 يوماً من التشتيل)؛ حيث انخفض كل من: المحتوى المائي للأوراق (%)، ارتفاع النبات (سم/نبات)، عدد الأوراق على النبات (ورقة/نبات)، المساحة الورقية (سم2)، مساحة المسطح الورقي الكلي للنبات (سم2/نبات)، الوزن النوعي للأوراق (غ/سم2)، دليل المساحة الورقية، المعدل الصافي لعملية التمثيل الضوئي (غ/م2/يوم) كما وازدادت شدة الإجهاد (Stress Intensity) وانخفضت قدرة النبات على التحمل (Stress Tolerance) بالمقارنة مع الشاهد والمعاملة بالتركيز (4 غ/هكتار). زادت، في المقابل، المعاملة بالتركيز (4 غ/هكتار) من نمو وتطور نباتات التبغ، والذي كان ملحوظاً عند أغلب المعايير المورفولوجية، المورفيزيولوجية والفيزيولوجية المقاسة بعد 10 أيام من التشتيل. نخلص مما سبق، بأن المبيد العشبي، جليفوسات، ذات تأثير شديد السلبية على نباتات التبغ وقد يؤدي إلى هلاك نسبة عالية من النباتات عند استخدامه كمبيد أعشاب بالتراكيز العالية، كما ويمكن استخدامه، في المقابل، لغرض تحسين نمو وتطور النباتات، كمحفز على الانقسام الخلوي، وعلى النمو والتطور النباتي عند اضافته بتركيز منخفض.